Pengelolaan BUMDES Harapan Berkembang Kabupaten Tegal - Rahmadiane, Ghea Dwi; Kamal, Bahri (Politeknik Ganesha Medan, 2024)
To encourage the realization of community participation, Bumdes administrators and village government must work together in planning programs and still consider existing social values, so that in carrying out development programs it can provide welfare to the community and be able to create strong community participation in Bumdes management. The purpose of this study was to determine community participation and its inhibiting factors in the management of Bumdes Harapan Berkembang. In this study using descriptive statistical analysis. The population in this study were Village Officials, Bumdes Management, and the people in the East Mejasem Village. The sample in this study was determined using the sampling technique used was purposive sampling, where samples were taken based on certain criteria. After analyzed with Cohen and Uphoff's theory which shows community participation in management activities, namely participation in planning, participation in implementation, participation in benefits, and participation in evaluation, it can be seen that community participation in Bumdes management was at the Degrees of Citizen Powers or Partnership, namely Bumdes Harapan Berkembang has achieved citizen power, so that at this level multi-stakeholder cooperation formed in formulating or implementing policies and programs. According to Arnstein, new participation really occurs when people have sufficient levels of wealth and the highest level of people's sovereignty was the occurrence of social control and citizen control in which important decisions and controllers of development in the hands of the people. There were factors that hinder the successful management of Bumdes Harapan Berkembang, namely internal and external factors.